Graph Theoretical Analysis of Functional Brain Networks in Healthy Subjects: Visual Oddball Paradigm - Kang Wei Thee; Humaira Nisar; Chit Siang Soh (IEEE Access, 2018)
This paper evaluates brain functional connectivity (FC) using Electroencephalography data from 18 healthy subjects using visual oddball paradigm. We have evaluated the effect of different oddball tasks in different time segments. We have also compared the brain FC between the resting state-task data and task-task data. The trials from oddball tasks were averaged to form grand-average event-related potential. Each epoch was divided into six segments with fixed time interval. Coherence was used to compute the pairwise connections between 10-20 electrodes and adjacency matrices were formed. The threshold of 0.9 was set to binarize the matrices and form undirected graphs. Graph parameters (node degree, network density, and betweenness centrality) were used to quantify the networks. Node degree within a brain lobe was summed to form a brain regional activation graph. Node betweenness centrality was used to study the dynamic changes of the hub nodes in different oddball tasks. Edge betweenness centrality was used to quantify the significant functional networks in different oddball tasks. Results show that 1) denser brain network was found in target with response (TR) case as compared with target with no response and no target no response cases especially over 3rd, 4th, and 5th time segments which are before and during P300 period. 2) Higher brain activity in terms of node degree is distributed over all brain regions for TR case than the other two cases. 3) It is also observed that the parietal node is significant for P300 response. 4) Interactions among parietal, central, and temporal regions are significant for motor response that is only observed for TR case. The present findings suggest that our methodology is able to identify differences in FC patterns elicited by different oddball tasks for different brain states in different time segments.